Effect of Climatic Conditions on Tree-Ring Widths in Black Locust (Robinia pseudoacacia L.) in the city of Wrocław - Robert Kalbarczyk (University of Zagreb, Faculty of Forestry and Wood Technology, 2016)
The response of trees to weather conditions, expressed in the tree-ring widths, depends on the extent of urbanization in the area. Specifi c climatic conditions in an urban heat island can be expected to result in growth differences to trees growing in non-urban areas. Accordingly, the aim of this study was to characterize the effect of climatic conditions on tree-ring widths of black locust in the city of Wrocław. Materials consisted of wooden discs taken from felled trees at four sampling sites (4 streets of Wrocław) at a height of 1.3 m from the ground. Meteorological data were obtained for the period 1971-2013 from the Institute of Meteorology and Water Management (IMGW) in Wrocław. Analysis of the multiannual period showed a significant negative trend in annual ring widths of black locust in the city of Wrocław. A code WROB was assigned to the chronology. The annual ring widths averaged 3.4 mm, ranging from 1.6 to 5.6 mm. In the urban conditions of Wrocław, the air temperature and precipitation significantly influenced the annual ring widths of black locust. The results indicate the need for further research on a larger number of samples.